2003
DOI: 10.1046/j.1365-2745.2003.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Transition probabilities from pollination to establishment in a rare dioecious shrub species (Rhamnus ludovici‐salvatoris) in two habitats

Abstract: Summary 1We elucidated the critical life stages and processes in the recruitment of Rhamnus ludovici-salvatoris , a dioecious shrub endemic to the Balearic Islands (western Mediterranean), populations of which have been shrinking in recent decades. We evaluated transition probabilities between all stages involved in regeneration from pollination to seedling recruitment, in order to determine the overall probability of an ovule in a flower becoming an established individual in a population. 2 We compared popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
123
6
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 39 publications
(55 reference statements)
15
123
6
2
Order By: Relevance
“…It is up to 2 m high, and its small leaves (the leaf area usually varies from 1 to 3 cm 2 ) are denticulate and elliptical to suborbicular. The species is mostly entomophilous and usually flowers during spring, with a peak at the end of April to mid-May [3]. As in R. alaternus, the flowers are pale yellow and grouped in racemes, and the fruit is a small drupe (diameter < 1 cm), usually bearing two seeds covered by an endocarp which opens when the fruit pulp is removed.…”
Section: Study Speciesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is up to 2 m high, and its small leaves (the leaf area usually varies from 1 to 3 cm 2 ) are denticulate and elliptical to suborbicular. The species is mostly entomophilous and usually flowers during spring, with a peak at the end of April to mid-May [3]. As in R. alaternus, the flowers are pale yellow and grouped in racemes, and the fruit is a small drupe (diameter < 1 cm), usually bearing two seeds covered by an endocarp which opens when the fruit pulp is removed.…”
Section: Study Speciesmentioning
confidence: 99%
“…Several studies have suggested that seedling survival during the early stages is a critical phase in seedling recruitment success [1][2][3]. In Mediterranean ecosystems, many reports have identified summer drought as one of the main causes of seedling mortality during their first year, when plants still have an underdeveloped root system [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant recruitment success depends on the success of individuals at different life-history stages (e.g., ovule, seed, seedling, adults) (Rey and Alcántara, 2000;Traveset et al, 2003). The need to studying those different lifehistory stages when looking for the demographic causes of narrow distributions has been recognized (Bevill et al, 1999) because it allows the identification of the stages where the mortality of potentially reproductive individuals is the highest, and thus of processes that might determine the colonization and persistence abilities of species.…”
Section: Introductionmentioning
confidence: 99%